2018
DOI: 10.2741/4582
|View full text |Cite
|
Sign up to set email alerts
|

SNPs and other polymorhisms associated with acaricide resistance in i Rhipicephalus microplus i

Abstract: Ixodicides resistance of ticks is one of the most important problems for the livestock industry in tropical and subtropical regions, mainly due to the increase in cases of multiple resistance in all families of the ixodicides used. Molecular markers such as single nucleotide polymorphisms (SNPs) has been proposed to identify the resistance to ixodicides in . Many studies have recently been conducted using SNPs and other types of molecular markers to determine if they are associated with resistance to different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 101 publications
(152 reference statements)
0
8
0
Order By: Relevance
“…This resistance is multifactorial and usually can be developed by several means through behavioral, biochemical, and metabolic ways ( Cossío-Bayúgar et al , 2018 ; Thangam and Kathiresan, 2021 ). That is why molecular markers have been developed to target the nucleotide sequence and genes responsible for this resistance as sodium channels, acetylcholinesterase, carboxylesterase, β-adrenergic octopamine receptor, and octopamine–tyramine in the insect as reported by Kumar (2019) and Aguilar et al (2018) .…”
Section: Discussionmentioning
confidence: 99%
“…This resistance is multifactorial and usually can be developed by several means through behavioral, biochemical, and metabolic ways ( Cossío-Bayúgar et al , 2018 ; Thangam and Kathiresan, 2021 ). That is why molecular markers have been developed to target the nucleotide sequence and genes responsible for this resistance as sodium channels, acetylcholinesterase, carboxylesterase, β-adrenergic octopamine receptor, and octopamine–tyramine in the insect as reported by Kumar (2019) and Aguilar et al (2018) .…”
Section: Discussionmentioning
confidence: 99%
“…This chemical acts as an octopamine receptor when applied to the tick, leading to reduced numbers of active neurons, resulting in tick paralysis and death [ 3 ]. The mechanism of tick resistance to acaricide is described by an increase in the tick’s metabolic activity that produces metabolic enzymes that detoxify any toxic substance as soon as possible before it gets to the target sites [ 35 ]. The current study found that the majority of the ticks were susceptible to exposure to different field-level concentrations of the acaricide amidines (49% at 250 ppm), OPs (33% and 47% at 300 ppm and 500 ppm, respectively), and SPs (44% and 23% at 150 ppm and 300 ppm, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The development of molecular markers for the detection and monitoring of acaricide resistance against different drug classes requires the identification of specific single nucleotide polymorphisms (SNP) in genes that are linked to drug resistance. There are several molecular markers that have been developed for the resistance monitoring of Rhipicephalus microplus and to lesser extent also for R. sanguineus which include mutations in the target genes of sodium channels, acetylcholinesterase, carboxylesterase, β-adrenergic octopamine receptor and octopamine-tyramine ( Klafke et al, 2017 ; Aguilar et al., 2018 ; Kumar, 2019 ). These markers allow the detection of resistance-associated genes within tick populations before they reach high levels.…”
Section: The Australian Paralysis Tick Ixodes Holocyclus ...mentioning
confidence: 99%